THE EFFECT OF SUCTION ON THE BOUNDARY LAYER SEPARATION OF A RETARDED BOUNDARY LAYER FLOW (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Boundary layer separation is one of the most drawback phenomena that reduces or even eliminates the lifting force generated by the flow over an airfoil. Boundary layer flow separation occurs due to an increasing adverse pressure gradient in the flow direction. Boundary layer theory fails to predict and describe this singularity where shear stress vanishes in the vicinity of the wall. To generate this phenomenon for a laminar flow over a flat plate in the presence of a pressure gradient, the linearly retarded flow of Howarth has been used. The decelerating non-similar free-stream velocity profile becomes increasingly S-shaped and finally separates downstream. The numerical solution of the considered flow reproduced the theoretical result reported by Howarth for the location of the separation point which is approximately (x sep / L   = 0.125). A suction strategy is applied over the wall which tends to shift the location of the separation point far downstream or completely suppresses its formation.